Ekologi Toponimi: Pengaruh Lingkungan terhadap Penamaan Desa di Kecamatan Larangan - Husnol Hotimah; Albaburrahim Albaburrahim (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research is motivated by the low level of knowledge of the people in the villages in Larangan District about the history and reasons behind the naming of their residential areas. Residents in the area generally only know the name of their village, but do not understand the history or origin of the naming. Therefore, this study aims to describe the ecology of toponymy from three perspectives, namely the manifestation aspect, the societal aspect, and the cultural aspect. This study uses a qualitative descriptive method, with data collection techniques through observation, interviews, and documentation. The results of this study reveal the ecology of toponymy based on environmental influences in the naming of villages in Larangan District. There are three villages, namely Montok Village, Trasak Village, and Peltong Village, which are included in the manifestation aspect category. Panaguan Village and Duko Village are included in the societal toponymy aspect, while Kaduara Barat Village, Taraban Village, and Grujugan Village are included in the cultural toponymy aspect.